UPSTREAM HYDRAULIC INTERCONNECTION STUDY OF GUNUNGKIDUL KARST AREA UNDERGROUND RIVERS - Sidauruk, Paston; Satrio; Pujiindiyati, Evarista Ristin; Aliyanta, Barokah (EKSPLORIUM, 2017)
Hydraulic interconnection of Jomblangan (Petung) cave with other caves and water discharges in Gunungkidul karst area has been investigated using tracer techniques and verified by stable isotopes and hydrochemical data interpretation. Many studies have been conducted to study the interconnections of underground rivers around Gunungkidul Karst area, most of them, however, focused on the interconnection of underground rivers around Bribin and Seropan caves. This is because of the development of micro hydro turbines to lift the water from underground river were still focused around Bribin and Seropan caves. Petung, located to the north of Bribin and Seropan caves, was believed to be one of the cave at the upstream of Bribin and Seropan caves, however, there is no evidence yet of the hydraulic interconnection between Petung cave with either Bribin or Seropan caves. The results of tracer technique at the current study, showed that there was no hydraulic interconnection between Petung cave with either Bribin and Seropan caves. On the other hand, the study showed an indication of a direct flow from Petung cave to Sriti and Beton springs. The travel times from Petung to Sriti and Beton springs were found to be around 2 and 10 hours, respectively. This finding is also in agreement with the results of chemical and stable isotopes analysis.